1990
DOI: 10.1177/000348949009901109
|View full text |Cite
|
Sign up to set email alerts
|

Tracheotomy in the First Year of Life

Abstract: Much has been written concerning complications of pediatric tracheotomies, but few studies have reviewed the complication rates of tracheotomies performed in the first 12 months of life. We reviewed the records of 60 patients who underwent tracheotomy in the first year of life between 1976 and 1988. This study includes 30 full-term infants and 30 premature infants, 16 of whom were very low birth weight preterm infants (less than or equal to 32 weeks' gestation and less than 1,500 g birth weight). Overall compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 11 publications
11
71
3
Order By: Relevance
“…Of the 33 unexcised granulomas, 16 (48%) resolved spontaneously; conversely, 18 (60%) of the 30 excised granulomas recurred. The median time to detection of recurrence was 3.4 months, with a range of 0.9 to 11.8 months (lower quartile, 1.5 months; upper quartile, 6.3 months).…”
Section: Resultsmentioning
confidence: 98%
“…Of the 33 unexcised granulomas, 16 (48%) resolved spontaneously; conversely, 18 (60%) of the 30 excised granulomas recurred. The median time to detection of recurrence was 3.4 months, with a range of 0.9 to 11.8 months (lower quartile, 1.5 months; upper quartile, 6.3 months).…”
Section: Resultsmentioning
confidence: 98%
“…Complication rate was also associated with the degree of prematurity in this study. Gianoli et al [21] found that the early postoperative complication rate in preterm infants was nearly double that of full-term infants. Crysdale et al [22] found that the younger the patient at the time of the procedure, the greater the risk to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Two infants died under unclear circumstances after discharge to other hospitals, both had a stent connected to a tracheotomy cannula. In this respect it may be mentioned that the mortality rate of a tracheotomy in infants is reported to be O-5% [22]. Complications, including mortality, are related to younger age and longer duration of the tracheotomy [14,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect it may be mentioned that the mortality rate of a tracheotomy in infants is reported to be O-5% [22]. Complications, including mortality, are related to younger age and longer duration of the tracheotomy [14,21,22]. The risks are probably further increased if a stent is connected to the cannula.…”
Section: Discussionmentioning
confidence: 99%